A STUDY ON THE SECOND YEAR STUDENTS’ SPEAKING ABILITY AT MA DAREL HIKMAH PEKANBARU - Wahidatul Hidayah, Hasti Noor; ', Novitri; ', Mahdum (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The objective of this descriptive research was to find out about students? speaking ability at MA Darel Hikmah Pekanbaru especially in narrative. The population of this research was the second year students? of MA Darel Hikmah Pekanbaru, particularly class XI IPA 1 that consist of 29 students chosen as the sample. The data were quantitative and speaking test used as the tools of collecting the data. The data were analyzed by calculating the score of the students that assessed by three raters and classifying to a certain level of ability based on the theory used. As the findings of this study, the average of the students? speaking ability is in good level, with the average score of 65.1. Among 29 students who took the test, 10 % of them are in excellent level, 59% of them are in good level, 31% of them are in moderate level, while 0% of them were in poor and very poor level. It means that they are able to speak English well, even though some of the students still lack in few aspects of speaking. Further research can focus on studying which method that might be useful for the students in improving their speaking ability particularly in each aspect of speaking.Keywords: speaking ability, narrative, personal experience